Determinants of Customer Satisfaction with Order Fulfilment among Customers of Bespoke Fashion in Nigeria (UNIZIK Journal of Marketing, 2024)
Due to the changes in customers’ preferences, fashion entrepreneurs are finding it difficult to satisfy the needs of the customers with the timing of delivery, the accuracy of the garments made contrary to expectation, the lac. In the fashion design context, customer is likely to be disappointed k of communication thereof and even a reactive effort to provide support for failed services. Therefore, the main objective of this study is to examine customer satisfaction with the order fulfilment process of female fashion entrepreneurs in Awka metropolis. The specific objectives are as follows to examine the effect of accuracy, timeliness of order fulfilment process, and order fulfilment communication and customer support service influence customer satisfaction with fashion entrepreneurs in Awka. The target population of this study are female consumers’ who had custom made garments in the past 12 months in Awka. The sample determined was determined at 126 using Topman formula and the hypotheses were tested using multiple regression analysis via SPSS. The result showed that order accuracy has a positive and significant effect on customer satisfaction (β = .74, t = 5.02, p < 0.01); and the timeliness of order fulfilment process on customer satisfaction with fashion entrepreneurs in Awka (β = .45, t =3.76, p < .05). While order fulfilment process communication and customer support service were not significant. Based on the findings, it was recommended that fashion designers should prioritize accuracy in customer orders to ensure customer satisfaction and also estimate how much time it takes to make specific kinds of garments and communicate it as a strategy to win and keep customers
Keywords: customer satisfaction, order fulfilment; timeliness; communication; customer support services; order accuracy